Comprehensive Study of Surgical Treated Lung Adenocarcinoma with Ground Glass Nodule Component - Xu, Ye (Med Sci Monit, 2019)
BACKGROUND: More and more patients with lung adenocarcinoma were detected with ground glass nodule (GGN) due to the popularity of low-dose spiral computed tomography (LDCT) recently. The clinicopathological characteristics and epidermal growth factor receptor (EGFR) mutation features were unclear. MATERIAL/METHODS: This retrospective study enrolled patients with surgical resected primary lung adenocarcinomas with GGN component. The clinicopathological data included age, gender, smoking history, tumor staging, lymph node staging, surgical methods, subtypes, thyroid transcription factor-1 (TTF-1) expression, EGFR gene mutation and follow-up records were investigated. RESULTS: There were 338 lung adenocarcinoma patients with GGN component eligible for our analysis: 219 patients (64.8%) harbored the EGFR mutation. In addition, the EGFR mutation rate was higher in patients with TTF-1+ than in patients with TTF-1− (72 out of 108 patients, 66.7% versus 147 out of 231 patients, 63.6%). In multivariable analysis, surgical procedure, tumor size, nodal stage, and subtype were still significant factors for relapse-free survival (RFS) while only subtype acted as the significant factor for overall survival (OS). In subgroup analyses, patients with TTF-1- had better prognosis in RFS (log-rank P=0.0142) when compared with those with TTF-1+ but not in OS (log-rank P=0.1113). Furthermore, patients with high-risk subtype had worse outcomes than those with low-risk subtype (RFS: log-rank P<0.0001; OS: log-rank P<0.0001). Patients who underwent limited resection experienced high risk of relapse (log-rank P<0.0001) while there was no statistical significance in OS (log-rank P=0.1644) between patients underwent lobectomy and those underwent limited resection. CONCLUSIONS: The prognosis of lung adenocarcinomas with GGN component depends mainly on the pathological subtype and there is no significant correlation between EGFR mutation and prognosis. Lobectomy should be performed actively in patients whose preoperative puncture biopsy or intraoperative freezing indicates an invasive or worse subtype. For postoperative patients, we should consider follow-up more frequently.